Lived Experiences of the Caregivers of Infants about Family-Centered Care in the Neonatal Intensive Care Unit: A Phenomenological Study - Zahra Hadian Shirazi; farkhondeh sharif; Mahnaz Rakhshan; Narjes Pishva; Faezeh Jahanpour (Mashhad University of Medical Sciences, 2018)
Background: Family-centered care (FCC) has recently been recognized as the most effective approach in pediatric and family care. Despite the emphasis of healthcare systems on commitment to the philosophy and application of FCC, the nature of this method remains unknown in the related studies. The present study aimed to describe and interpret the experiences of professional and familial caregivers about FCC in the neonatal intensive care unit (NICU) to reveal its structure and essence. Methods: The study was conducted using Van Manen's phenomenological approach on 18 participants, including 10 professional and eight familial caregivers, who were interviewed. In addition, the interactions between the caregivers during the FCC practice were observed closely. Data were collected from the interviews, and the field notes were transcribed. Data analysis was performed using Van Manen's thematic analysis. Results: Four main themes and 12 subthemes emerged in the study. Experiences of the caregivers about FCC were manifested through the themes of 'restoring stability' (subthemes: 'reconstituted family', 'comprehensive advocacy', and 'meta-family interaction'), 'oriented coalition' (subthemes: 'family as a care partner', 'professional group action', 'unity of action in caregivers', and 'collaborative space governance'), 'dynamics of care' (subthemes: 'family as an agent for the advancement of professional caregivers', 'perceived status of problem-solving', and 'confrontation of caregivers'), and 'empowering the family caregivers' (subthemes: 'accompanying to learn' and 'functional evolution'). Conclusion: According the results, FCC is a dynamic care intervention, which is established through purposeful interactions between heterogeneous group members (professional and familial caregivers) in order to achieve care goals and create balance in all caregivers. Moreover, the approach enables familial caregivers to play their role efficiently. Application of this comprehensive care requires the attention of healthcare policymakers and managers to provide the proper context for optimal care provision in the NICU.